The Authority of The Prosecutor's Office in Supervising Corporate Legal Compliance With Environmental Regulations in Indonesia - Dardiansyah Dardiansyah; Dewi Astutty Mochtar; Ghufron Ghufron (International Journal of Law and Society, 2025)
This study examines the authority of the Attorney General's Office in supervising corporate compliance with environmental regulations under Law No. 32 of 2009 and within the concept of Ius Constituendum. Employing a normative legal research methodology, the study integrates the Statute Approach and a legal concept analysis approach. The Statute Approach analyzes laws and regulations, while the legal concept analysis combines analytical and conceptual dimensions to address gaps in legal interpretation. The research highlights the critical role of the Attorney General's Office in enforcing environmental law, particularly in addressing corporate violations that contribute to environmental degradation in Indonesia. Findings reveal that despite its strategic role, limited human resources and technical capacity hinder effective supervision. To strengthen this role, the study recommends expanding the Attorney General's authority to include preventive, civil, administrative, and criminal enforcement. Additionally, enhancing human